Impact of International Trade on Nigeria Economic Growth: Evidence on Trade Cost: Array - Ajayi, Babajide; Oguntomi, Emmanuel (Acta Universitatis Danubius. Œconomica, 2022)
This study investigated the impact of international trade on Nigerian economic growth, empirical evidence on trade cost. The ordinary least square technique was used to analyse data from 1960 to 2021. The study specifically focused on the impact of trade cost on economic growth in Nigeria, by grounding it on the Ricardian theory of comparative advantage. The econometric analyses of augmented dickey-fuller unit root test, error correction model, pair-wise granger causality test, and fully modified ordinary least square test were conducted. The FMOLS results showed that the consumer price index (CPI) and inflation consumer prices (ICP) have a significant negative effect on GDP. Thus, trade cost has adverse impact on Nigeria economic growth on the long run. On the short run, only consumer prices index (CPI) has positive impact on gross domestic product (GDP) while inflation consumer prices (ICP) has negative impact on gross domestic product (GDP), but the relationship is not statistically significant. It is recommended that there is need for the government to strengthen the monetary policy as to maintain price stability.